Computerized Exercises to Promote Transfer of Cognitive Skills to Everyday Life - Vianin, Pascal (Frontiers in Psychiatry, 2016)
In recent years, computerized and non-computerized cognitive remediation programs have been designed for both individual and group settings. We believe however that a common misconception lies in considering the efficiency of a cognitive remediation therapy as resulting from the sole use of a computer. This omits that metacognitive skills need also to be trained throughout the remediation phase. RECOS is a theory-based therapeutic approach designed to promote the transfer of cognitive skills to functional improvements. It involves working with one person at a time using both paper/pencil tasks and a set of interactive computer exercises. Paper/pencil exercises are used to promote problem solving techniques and to help patients to find and appropriate suitable strategies. During the following computerized one-hour session, therapists guide participants to the procedural dimension of the action which refers to knowledge about doing things and relies on retrospective introspection. We assume that each patient has a rich and underestimated procedural knowledge he/she is not aware of. By providing complex and interactive environments, computerized exercises are recommended to bring this knowledge to light. When strategies used by the participant become conscious, conditional knowledge determines when and why to use them in real life situations.